Contradiction or Contrariety? : Cirne-Lima and the need to correct Hegel’s alleged circular system (Revista Eletrônica Estudos Hegelianos, 2024)
This is a challenge to one of the central interpretational theses that Cirne-Lima defends on Hegel: that we should read "contradiction" as "contrariety". At first, I reconstruct Cirne-Lima’s interpretation and raise two critiques: (i) Cirne-Lima ignores the origin of the concept "contradiction" as applied to statements of conceptual identity; (ii) Cirne-Lima only pays attention to one type of incompatibility involved in the "negation" that constitutes contradiction and forgets Hegel’s thesis on the “bound return to the ground”. In the final parts of my paper, I discuss the consequences of Cirne-Lima’s interpretation. The consequence of (i) is the development of an interpretation that doesn’t regard anything beyond what Hegel calls "external reflection" ("is of predication") and ignores the role of "contradiction" in "inner reflection" ("is of identity"). That of (ii) is the interpretation of "contradiction" as a mere "play of opposites". I suggest that this last constraint is analogous to what Brandom calls "material incompatibility" and completely misses one of the main dimensions of Hegel’s “negative”: self-referential. To support my argument (i) I rely on Pippin’s remarks on the Logic of Essence and, in the case of (ii), Bordignon’s point that to be self-referential is a constitutive dimension of "determinate negation".